SUCCESS OF IMPLEMENTING COOPERATIVE LEARNING MODELS IN SCHOOLS - Rahmatika, Siti; Olii, Rahmat; Kadhapy, Moh. (JCI Publisher, 2025)
Cooperative learning is an instructional approach that emphasizes collaboration among students in small groups to achieve shared academic goals. This method not only enhances learning outcomes but also fosters social skills, individual responsibility, and mutual respect. This article explores the fundamental concepts of cooperative learning, its underlying principles, and several popular models such as Student Teams Achievement Division (STAD), Jigsaw, and Think-Pair-Share. The discussion also highlights the advantages and challenges of implementing this method in classroom settings. The findings indicate that cooperative learning increases student engagement, learning motivation, and conceptual understanding. Therefore, cooperative learning serves as an effective strategy for creating an active, participatory, and meaningful learning environment.